PEMANFAATAN TEKNOLOGI DIGITAL OLEH GURU DALAM PEMBELAJARAN SEBAGAI UPAYA PENJAMINAN MUTU DI SMPN 39 SAMARINDA: TANTANGAN DAN PELUANG - Madzkuri, Muhammad Redza; Bahrani, Bahrani; Nisa, Rahmatiana Azizatun (Jurnal Manajemen Pendidikan, 2025)
Utilization of digital technology by teachers as part of efforts to ensure the quality of education at SMP Negeri 39 Samarinda. The background of this study is the challenges in implementing digital transformation in schools, especially in integrating technology into quality teaching practices. A qualitative case study approach was used, with data collected through observation, in-depth interviews, and documentation involving teachers, school leaders, and internal policy documents. The results of the study indicate that teachers have adopted various digital platforms such as Google Classroom, Quizizz, and Google Forms in planning, implementing, and evaluating learning. This utilization has increased student participation, accelerated the learning assessment process, and supported transparency in the delivery of learning. In addition, Islamic values ​​have been successfully integrated into digital media as part of character education. However, this study also identified several challenges, including limited infrastructure, varying levels of digital literacy among teachers, and the absence of detailed technical regulations. The novelty of this study lies in the integration of the digital pedagogy approach with the instillation of religious values ​​within the framework of the school's internal quality assurance system. This study offers theoretical insights and practical recommendations for policy development and teacher training to strengthen holistic and sustainable digital transformation in education.